MAXIMIZING JUNIOR HIGH EFL SPEAKING: THE IMPACT OF ROLE PLAY ON CLASSROOM COMMUNICATION ACHIEVEMENT - Sulistyahadi Sulistyahadi (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
Speaking proficiency in English is a fundamental aspect of communicative competence and academic achievement; however, many junior high school students show limited progress due to the lack of interactive and communicative teaching strategies. This study aims to examine the effectiveness of the role-play technique as a pedagogical intervention to enhance students’ speaking skills among first-year learners at SMPN 03 Karang Ploso Satu Atap. The research employed a quasi-experimental design involving 25 students who participated in pre-test and post-test assessments covering four components of speaking ability, namely fluency, vocabulary, pronunciation, and grammar. The quantitative results indicated a substantial improvement in students’ speaking performance, with the mean score increasing from 53.6 in the pre-test to 63.2 in the post-test. The statistical analysis using a t-test revealed that the obtained value (t = 7.10) exceeded the critical value (t = 2.064), confirming that the improvement was statistically significant. These findings demonstrate that role play is an effective instructional technique for promoting speaking proficiency, increasing students’ motivation, and encouraging active participation in the learning process. Therefore, this study recommends the integration of role-play activities into English language teaching practices to strengthen students’ communicative competence at the junior secondary school level.